Fly and Treat: Endovascular Treatment of Ruptured Aneurysms at an Insular Tertiary Center - Almeida Xavier, S (2023)
(Objectives) Aneurysmal subarachnoid hemorrhage (aSAH) is a life-threatening condition associated with poor outcomes. Early intervention is critical, particularly in low-volume hospitals, which are advised to transfer aSAH patients to high-volume centers. This study examines a novel protocol implemented in 2016 at Região Autónoma da Madeira, a Portuguese island. It involves the mobilization of experienced neurointerventionalists from high-volume hospitals to provide aSAH treatment. (Methods) We conducted a retrospective analysis on 30 aSAH patients who underwent endovascular treatment at the island center between November 2016 and April 2022. Additionally, we included a comparison group of 74 aSAH patients, treated with the endovascular approach at Hospital de Braga (high volume center at Portugal mainland). (Results) There was no statistical difference in patients' clinical severity between both hospitals (median WFNS score of 1). Although 90 % of patients in the novel protocol group received treatment within 3 days, we observed a significant delay compared to Hospital de Braga. Rates of aneurysm occlusion and intra-procedure complications between the two groups were similar. At the 3-months follow-up, there were no statistically significant differences between groups regarding patients that achieved a modified Rankin score of 2 or less. However, the island center exhibited a significantly higher mortality rate. (Conclusions) Overall, our results suggest that making the neurointerventionalist fly to an insular center is feasible and allows most patients to be treated within the first 72 h, as recommended. We highlight some potential recommendations for implementing this model and discuss possible causes that might justify the high mortality rate.